2019
DOI: 10.1111/pre.12410
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and growth of Ulva ohnoi and Ulva pertusa (Ulvophyceae) under high light and high temperature conditions, and implications for green tide in Japan

Abstract: SUMMARY The macroalga Ulva ohnoi constitutes a considerable fraction of green tides in coastal areas of Japan, but little is known about the physiological characteristics of this species. To investigate the environmental factors that promote the formation of green tides, we tested the responses of U. ohnoi and another common Japanese species, Ulva pertusa, to various levels of irradiance at different water temperatures. Because the two species are morphologically similar, we identified them using the PCR‐restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Another explanation could be related to the water temperatures to which each species was adapted. It is known that this environmental variable affects the growth rate of seaweeds, with different species exhibiting different optimal temperatures for maximum growth (Mantri et al, 2011;Nakamura et al, 2020). U. ohnoi colleted in the lagoons could have been more adapted to the warmer Table 1.…”
Section: /6mentioning
confidence: 99%
“…Another explanation could be related to the water temperatures to which each species was adapted. It is known that this environmental variable affects the growth rate of seaweeds, with different species exhibiting different optimal temperatures for maximum growth (Mantri et al, 2011;Nakamura et al, 2020). U. ohnoi colleted in the lagoons could have been more adapted to the warmer Table 1.…”
Section: /6mentioning
confidence: 99%
“…Entretanto, a Ulva spp. também se mostra extremamente adaptável a condições de menor exposição de luz, como, por exemplo, em florações algais, onde parte dos organismos é exposta a uma grande intensidade de luz e calor na superfície e, em camadas inferiores, a condições de baixíssima luminosidade (Nakamura et al 2020).…”
Section: Discussionunclassified
“…However, U. ohnoi is a recently reported green-tide-forming species, and research on its ecophysiological responses to physicochemical conditions is very limited (e.g. Mata et al, 2016;Nakamura et al, 2020;Zanolla et al, 2019). This species has been reported to cause widespread green-tides, especially along the coast of Jeju Island, South Korea (Kang et al, 2019), and as the spatiotemporal distributions and intensities of its blooms are increasing, it is becoming more important to better understand their causes and consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although U. ohnoi was identified as a new species (Hiraoka et al, 2006), the distribution of this species has already been reported in various region of the world (Guiry and Guiry, 2020), which suggests that U. ohnoi has a strong tolerance to variability in environmental conditions. However, most ecophysiolocial studies on U. ohnoi have focused on the effects of temperature and light intensity (e.g., Mata et al, 2016;Nakamura et al, 2020;Zanolla et al, 2019), and little is known about its tolerance to changes in both seawater temperature and CO 2 (and pH) conditions.…”
Section: Introductionmentioning
confidence: 99%